2020
DOI: 10.1017/s0022149x20000309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of road salt on a free-living trematode infectious stage

Abstract: Many temperate freshwater habitats are at risk for contamination by run-off associated with the application of road de-icing salts. Elevated salinity can have various detrimental effects on freshwater organisms, including greater susceptibility to infection by parasites and pathogens. However, to better understand the net effects of road salt exposure on host–parasite dynamics, it is necessary to consider the impacts on free-living parasite infectious stages, such as the motile aquatic cercariae of trematodes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
(105 reference statements)
3
10
0
Order By: Relevance
“…Previous studies have shown that the fecundity and survival of snails are adversely affected by salinities as low as 1 ppt, with significant reductions occurring between 3.5 and 4.5 ppt resulting in progressive elimination of snails [ 18 , 52 ]. Additionally, our result demonstrating higher cercarial survival rates at intermediate seawater concentrations is supported by previous studies, however, the salinity at which survival peaks varies among different host and parasite species and strains [ 36 , 53 , 54 ]. Despite the observed decreases in snail fitness and parasite transmission at higher seawater concentrations, production of infective cercariae proceeded successfully in concentrations of seawater up to 5.7 ppt suggesting that although parasite burden may be lessened, infections could still occur as sea levels rise [ 15 and the current study].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that the fecundity and survival of snails are adversely affected by salinities as low as 1 ppt, with significant reductions occurring between 3.5 and 4.5 ppt resulting in progressive elimination of snails [ 18 , 52 ]. Additionally, our result demonstrating higher cercarial survival rates at intermediate seawater concentrations is supported by previous studies, however, the salinity at which survival peaks varies among different host and parasite species and strains [ 36 , 53 , 54 ]. Despite the observed decreases in snail fitness and parasite transmission at higher seawater concentrations, production of infective cercariae proceeded successfully in concentrations of seawater up to 5.7 ppt suggesting that although parasite burden may be lessened, infections could still occur as sea levels rise [ 15 and the current study].…”
Section: Discussionsupporting
confidence: 90%
“…Approximately 20 cercariae were placed into individual wells with 1ml of the four salinity treatment solutions. Cercariae survival was checked at 4h, 8h, 12h, and 24h after release from the snail, and cercariae were removed if little to no movement was detected [ 35 , 36 ]. Following the 24h check, all cercariae were euthanized with ethanol and counted to determine the exact number of cercariae in each trial.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the fecundity and survival of snails is adversely affected by salinities as low as 1 ppt, with significant reductions occurring between 3.5 and 4.5 ppt resulting in progressive elimination of snails [14,29]. Additionally, our result demonstrating higher cercarial survival rates at intermediate seawater concentrations is supported by previous studies, however, the salinity at which survival peaks varies among different host and parasite species and strains [3032]. Despite the observed decreases in snail fitness and parasite transmission at higher seawater concentrations, production of infective cercariae proceeded successfully in concentrations of seawater up to 5.7 ppt suggesting that although parasite burden may be lessened, infections could still occur as sea levels rise [15 and the current study].…”
Section: Discussionsupporting
confidence: 90%
“…The free-living cercarial life stage of trematodes is exposed to the environment of their hosts during transmission, leaving them vulnerable to exposure to environmental contaminants (Pietrock and Marcogliese 2003;Sures et al 2017). Indeed, exposure of trematodes to a wide range of contaminants and toxicants has been shown to induce mortality in these freeliving life stages (Morley et al 2003;Rohr et al 2008a;Hua et al 2016;Sures et al 2017;Buss et al 2019Buss et al , 2020Milotic et al 2019Milotic et al , 2020. In the present study we examined the potential for direct lethal effects of microplastics on cercariae.…”
Section: Discussionmentioning
confidence: 99%